The Influence of Compensation on Employee Performance through Work Motivation - Syaiful Bachri Chaidier; Maman Suratman (Journal of Research in Social Science and Humanities, 2025)
This study aims to empirically examine the effect of compensation on employee performance through work motivation among employees of Delima Asih Sisma Medika Hospital. The proposed hypotheses are: (1) there is a significant positive effect of compensation on employee performance; (2) there is a significant positive effect of compensation on work motivation; (3) there is a significant positive effect of work motivation on employee performance; and (4) compensation affects employee performance through work motivation. The research population consists of employees of Delima Asih Sisma Medika Hospital, with a total sample of 136 respondents selected using simple random sampling. Data collection employed Likert-scale instruments, namely the employee performance scale, the compensation scale, and the work motivation scale. Data were analyzed using SPSS with hypothesis testing conducted through PROCESS.The research results show that: (1) The description of the level of compensation perception of employees at Delima Hospital is Low; (2) The description of the level of employee performance at Delima Hospital is Very Low; (3) The description of the level of work motivation of employees at Delima Hospital is Very Low; (4) There is a significant positive effect of compensation on employee performance; (5) There is a significant positive effect of compensation on work motivation; (6) There is a significant positive effect of work motivation on employee performance; and (7) There is a significant effect of compensation on employee performance through work motivation.